MO269: The Frequency and Aetiology of Repeated Acute Kidney Injury Episodes Determines the Degree of Renal Damage. (3rd May 2022) - Mercado-Hernandez, Joana; Fuentes-Calvo, Isabel; Sancho Martinez, Sandra M; Lopez-Hernandez, Francisco J; Martinez Salgado, Carlos
Abstract: BACKGROUND AND AIMS: Chronic kidney disease (CKD) is the most serious health problem and constitutes the 16th leading cause of death worldwide. Multiple studies have identified acute kidney injury (AKI) as a risk factor for the development and progression of CKD [1 ]. Despite extensive investigation of AKI and CKD in experimental models, the underlying mechanisms of the transition from AKI to CKD remain unclear. It is known that after an AKI episode, maladaptive responses may occur resulting in structural and fuctional abnormalities as parenchymal inflammation, tubular cell death, accumulation of extracellular matrix, and decreased glomerular filtration rate, among others [2 ]. We hypothesized that after the combination of different renal insults, the mechanisms of adaptative repair could be less effective causing renal structural abnormalities that might not be detected by common clinical parameters but could lead to CKD. METHOD: We used 8-week-old, male Wistar rats. Animals were divided into four experimental groups: 'Control' group: SHAM-operated rats, which received saline solution, i.p.; 'CDDP5-I/R' group: 5 mg/kg cisplatin i.p., and after renal function normalization, 60-min ischemia-reperfusion to the left kidney; 'Ctrl-I/R-I/R' group: 60-minute renal ischemia-reperfusion to the left kidney, and 2 weeks later 60-min ischemia-reperfusion to the right kidney; 'CDDP5-Ctrl-I/R' group: 5 mg/kg cisplatin i.p, and 2 weeks after renal function normalization, 60-min ischemia-reperfusion. Blood and urine samples were collected at: day 0 (basal); day 4 (AKI development); day 8 (normalized renal function); day 9 (1 day after ischemia); days 56 and 90. Renal function was analyzed through the levels of plasma creatinine concentration (pCr), creatinine clearance, blood urea nitrogen and proteinuria, which were measured with colorimetric methods. Animals were sacrificed at days 56 and 90. Tissue samples were stained with Masson's trichrome, Sirius Red, Periodic Acid Schiff and Hematoxylin-–Eosin for histological analysis. RESULTS: The combination of different experimental AKI episodes and the timeframe between those episodes were related to the extent of renal structural alterations, even though renal function was apparently normal. The 'CDDP5-Ctrl-I/R' group presented the highest level of structural abnormalities. In addition, in those groups in which an AKI was induced by CDDP5, more structural damage was detected than in the 'Ctrl-I/R-I/R' group. CONCLUSION: The frequency of AKI episodes, the kind of insult and their combination determine the amount and degree of tissue damage which, however, is not correlated with a decline in renal function (determined by pCr or creatinine clearance, blood urea nitrogen or proteinuria). These subclinical alterations might be related to a poor prognosis and are a risk factor for the progression of CKD; therefore, new tools to determine renal function are needed to prevent the progression and mortality of the disease.